Do informal musical activities shape auditory skill development in preschool-age children? - Putkinen, Vesa J.; Saarikivi, Katri A.; Tervaniemi, Mari (Frontiers in Psychology, 2013)
The influence of formal musical training on auditory cognition has been well established. For the majority of children, however, musical experience does not primarily consist of adult-guided training on a musical instrument. Instead, young children mostly engage in everyday musical activities such as singing and musical play. Here, we review recent electrophysiological and behavioral studies carried out in our laboratory and elsewhere, which have begun to map how the developing auditory skills are shaped by such informal musical activities both at home and in playschool-type settings. Although more research is still needed, the evidence emerging from these studies suggests that, in addition to formal musical training, also informal musical activities can influence the maturation of auditory discrimination and attention in preschool-age.